A Broad Profile of Co-Dominant Epitopes Shapes the Peripheral Mycobacterium tuberculosis Specific CD8+ T-Cell Immune Response in South African Patients with Active Tuberculosis - Axelsson-Robertson, Rebecca (Public Library of Science, 2013)
We studied major histocompatibility complex (MHC) class I peptide-presentation and nature of the antigen-specific CD8+ T-cell response from South African tuberculosis (TB) patients with active TB. 361 MHC class I binding epitopes were identified from three immunogenic TB proteins (ESAT-6 [Rv3875], Ag85B [Rv1886c], and TB10.4 [Rv0288], including amino acid variations for Rv0288, i.e., A10T, G13D, S27N, and A71S for MHC allotypes common in a South African population (e.g., human leukocyte antigen [HLA]-A*30, B*58, and C*07). Inter-allelic differences were identified regarding the broadness of the peptide-binding capacity. Mapping of frequencies of Mycobacterium tuberculosis (M. tb) antigen-specific CD8+ T-cells using 48 different multimers, including the newly constructed recombinant MHC class I alleles HLA-B*58:01 and C*0701, revealed a low frequency of CD8+ T-cell responses directed against a broad panel of co-dominant M. tb epitopes in the peripheral circulation of most patients. The antigen-specific responses were dominated by CD8+ T-cells with a precursor-like phenotype (CD45RA+CCR7+). The data show that the CD8+ T-cell response from patients with pulmonary TB (prior to treatment) is directed against subdominant epitopes derived from secreted and non-secreted M. tb antigens and that variant, natural occurring M. tb Rv0288 ligands, have a profound impact on T-cell recognition.